Nematicidal glycosylated resorcylic acid lactones from the fungus Pochonia chlamydosporia PC-170 and their key biosynthetic genes - Li, Zeyu; Luo, Ning; Zhang, Wenwen; Khan, Raja Asad Ali; Ling, Jian; Zhao, Jianlong; Yang, Yuhong; Mao, Zhenchuan; Xie, Bingyan; Zhou, Ligang; Li, Yan (Frontiers in Microbiology, 2024)
Chemical study of the nematicidal biocontrol fungus Pochonia chlamydosporia PC-170 led to discovery of six resorcylic acid lactones (RALs), including three nematicidal glycosylated RALs, monocillin Ⅵ glycoside (1), colletogloeolactone A (2) and monocillin Ⅱ glycoside (3), and three antibacterial non-glycosylated RALs, monocillin Ⅵ (4), monocillin Ⅳ (5) and monocillin Ⅱ (6). The planar structure of the new compound monocillin Ⅵ glycoside (1) was elucidated using HRESIMS and NMR data, and its monosaccharide configuration was further determined through sugar hydrolysis experiment and GC-MS analysis method. Furthermore, their two biosynthetic-related PKS genes, pchE and pchI, were identified through the gene knockout experiment. The glycosylated RALs 1-3 exhibited nematicidal activity against Meloidogyne incognita, with LC50 values of 94, 152 and 64 μg/mL, respectively, and thus had great potential in the development of new nematicidal natural products to control M. incognita in the future.